2022
DOI: 10.24269/ekuilibrium.v17i1.4460
|View full text |Cite
|
Sign up to set email alerts
|

Total Factor Productivity Calculation of The Indonesian Micro and Small Scale Manufacturing Industry

Abstract: The purpose of this research is to determine the total factor productivity (TFP) of Indonesia's micro and small-scale manufacturing industries. The production function estimation approach established by Levinsohn-Petrin as the basis for computing TFP is employed in this study, with value added as the dependent variable and the value of labor costs and capital value proxied by the value of investment as the independent variables. This study uses secondary data from the Central Statistics Agency (BPS), which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
6
0
9
Order By: Relevance
“…Riset berbeda, menemukan bahwa pangan yang diukur melalui subsektor tanaman pangan memiliki tingkat keterkaitan baik daya tarik maupun daya dorong yang rendah terhadap sektor di hulu maupun di hilir, sedangkan dari sisi multiplier effect, pengganda output pangan jauh lebih besar dibandingkan pengganda pendapatan (Choiroh et al, 2020;Hamijaya & Suryaman, 2023a, 2023bSetiawan et al, 2021). Meskipun sektor pangan bukanlah leading sector tapi kemampuan serapan tenaga kerjanya tidak kalah dengan sektor industri (Djulius et al, 2019;Haris et al, 2018;Rostiana et al, 2022).…”
Section: Pendahuluanunclassified
“…Riset berbeda, menemukan bahwa pangan yang diukur melalui subsektor tanaman pangan memiliki tingkat keterkaitan baik daya tarik maupun daya dorong yang rendah terhadap sektor di hulu maupun di hilir, sedangkan dari sisi multiplier effect, pengganda output pangan jauh lebih besar dibandingkan pengganda pendapatan (Choiroh et al, 2020;Hamijaya & Suryaman, 2023a, 2023bSetiawan et al, 2021). Meskipun sektor pangan bukanlah leading sector tapi kemampuan serapan tenaga kerjanya tidak kalah dengan sektor industri (Djulius et al, 2019;Haris et al, 2018;Rostiana et al, 2022).…”
Section: Pendahuluanunclassified
“…Efforts to reduce CO2 emissions and switch to cleaner energy sources are important steps in addressing global climate change. However, along with that, the Government of the Republic of Indonesia must also consider sustainable economic growth in order to be able to answer the social and economic needs of the community (Pasaribu et al, 2023;Rostiana et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…One of the previous studies discussed the total factor productivity in micro and small industries. The researcher found that the total factor productivity in the micro industry is greater than that in the small industry [4]- [6]. The discussion regarding the productivity of micro and small industries can be narrowed down, one of which is labor productivity.…”
Section: Introductionmentioning
confidence: 99%